THE IMPLEMENTATION OF SELF-REGULATED LEARNING TOWARDS EFL STUDENTS SPEAKING SKILLS: SENIOR HIGH SCHOOL CASE - Fizariyah Sukma (Inspiring: English Education Journal, 2022)
Mastering speaking skills needs a long process and a suitable way of learning. In Indonesia itself, the students still have a high dependency on the teacher which makes them being more difficult to learn speaking skills with that behavior. This study purposes a learning model namely Self-Regulated Learning to reduce the students dependency on the teacher. Therefore, this study aims to describe the implementation of Self-Regulated Learning and the students perception as well. The sample population of this study is 22 students of 10th graders at Senior High School 1 Sampang and one of the English teacher there with purposive sampling. The researcher gave a questionnaire, a self-reflection diary, and interviewed the samples to collect the data. It was found that Self-Regulated Learning is a suitable and helpful learning model that makes the students can organize their learning, know themselves better, and improve their speaking skills. Meanwhile, the teacher also should accompany the students by creating a good learning environment and building a strong relationship with each other. The teacher also should concern with students who have low motivation because they are less of improvement in implementing Self-Regulated Learning.